Biventricular Failure due to Stress Cardiomyopathy after Pericardiectomy for Constrictive Pericarditis - Elliott M. Groves; Jin Kyung Kim (Case Reports in Medicine)
Importance. Constrictive pericarditis is a rare clinical entity that frequently necessitates surgical intervention. Here we present a case of biventricular failure due to stress cardiomyopathy after pericardiectomy. This is an extremely rare complication that is not well described and does not have a definitive mechanism. Observations. A 40-year-old Ecuadorian woman who was found to have constrictive pericarditis due to Mycobacterium tuberculosis infection was referred to our institution. The presence of constrictive pericarditis was confirmed by echocardiography, computed tomography, magnetic resonance imaging, and cardiac catheterization. Following pericardiectomy, the patient developed biventricular failure consistent with stress cardiomyopathy (Takotsubo cardiomyopathy), based on the echocardiographic assessment of the ventricles, which demonstrated an akinetic apex and hyperactive base in both ventricles, the absence of significant epicardial coronary atherosclerosis, and prompt normalization of the cardiac function after intensive medical therapy. Conclusions and Relevance. Biventricular failure in the form of stress cardiomyopathy after pericardiectomy in the manner presented here has not been previously described in the literature. While postulations as to the cause of single ventricle dysfunction have been described, the exact mechanism is unclear and current theories do not explain the clinical features in this case of stress cardiomyopathy after pericardiectomy.